Tantangan Diagnosis Dan Tatalaksana Glucocorticoid Withdrawal Syndrome Dengan Diagnosis Banding Sindrom Cushing: Sebuah Laporan Kasus - Made Adikosha Pranata; Wira Gotera; Ida Bagus Aditya Nugraha; Karlina Isabella; Ni Made Dwi Adnyani; Ni Wayan Meindra Wirtayani (CV. AKBAR PUTRA MANDIRI, 2025)
Glucocorticoid withdrawal syndrome (GWS) presents a significant diagnostic and therapeutic challenge due to overlapping clinical features with Cushing's syndrome. We report the case of a 52-year-old man who presented with severe joint pain, swelling, myalgia, anorexia, nausea, and notable clinical features including moon face, central obesity, and violaceous striae, suggestive of chronic glucocorticoid exposure. His medical history revealed long-term, unsupervised glucocorticoid use through over-the-counter analgesics. Laboratory investigations demonstrated progressive leukocytosis, marked neutrophilia, elevated procalcitonin levels indicative of systemic infection, significant electrolyte disturbances (hyponatremia, hypokalemia), impaired glucose metabolism, and moderate renal dysfunction. Cardiac evaluation revealed atrial fibrillation with rapid ventricular response, congestive heart failure, and left ventricular hypertrophy, consistent with chronic glucocorticoid exposure complications. Initial basal cortisol testing showed normal-low levels, necessitating further confirmation through ACTH stimulation testing to differentiate between glucocorticoid-induced adrenal insufficiency and endogenous hypercortisolism. Management strategies included carefully tapered intravenous glucocorticoids transitioning to oral methylprednisolone, intensive insulin therapy for glycemic control, aggressive treatment of infection, and meticulous fluid-electrolyte management, resulting in clinical and biochemical improvement. The complexity of this case underscores the necessity for a thorough, multidisciplinary approach involving endocrinologists, cardiologists, internists, and nutritionists to ensure optimal management of GWS, prevent adrenal crises, and mitigate long-term cardiovascular and metabolic complications